Efficacy of 1-β-d-Ribofuranosyl-1,2,4-Triazole-3-carboxamide Against Influenza Virus Infections in Mice - Durr, F. E. (1975)
1-β-d-Ribofuranosyl-1,2,4-triazole-3-carboxamide (ribavirin) was effective against strains of influenza virus types A and F, whereas amantadine hydrochloride was effective only against strains of influenza virus type A. Dose-related protective effects against lethal influenza infections in mice were obtained with single oral doses of 25 to 400 mg of ribavirin per kg administered at the time of virus inoculation or up to 24 h thereafter. Therapeutic indexes (maximum tolerated dose/median effective dose) against various strains of influenza virus ranged from 5 to 35. With multiple-dose treatment initiated immediately after virus inoculation, oral doses as low as 12 to 25 mg/kg twice daily also afforded significant protection. Treatment with ribavirin inhibited the growth of influenza virus in the lungs of mice and delayed by about 24 h the attainment of maximal viral titers, which in nontreated mice were reached within 24 to 48 h. Inhibition of viral growth was correlated with a suppression of lung consolidation. Ribavirin appears to exert its protective effects against influenza infections by inhibiting virus growth, thereby preventing virus titers from reaching levels that result in massive lung tissue destruction and death of the mice.